A review on tunnel-pile interaction applied by physical modeling - Sohaei, H. (Springer, 2020)
Tunneling close beneath piles is becoming increasingly common in densely populated areas. It has therefore become important to understand more about the mechanism of the soil movements and interaction between the tunnel and piles. Physical modeling, which can replicate the actual tunnel construction and related process, is most widely used to investigate the mechanism of pile–tunnel interaction and validate the predicted results by other solutions. This paper presents a review of studies on that matter followed by a quantitative comparison of the pile movements and loads due to tunneling. In this regard, all previous studies of physical modeling of the prototype including single and multiple gravity tests have been reviewed. In addition, modeling of pile–tunnel interaction has been categorized into two groups of tunneling with the existence of single pile and group of piles. Finally, the results and findings of the most recent studies in the field of tunnel–pile interaction have been discussed. Collecting and analyzing of these data provide a better understanding of the interaction as well as indicating where further research is needed.